The role of Ashwagandha in modulating gut parameters in dogs—a randomized double-blind placebo-controlled trial - Bharani, Kala Kumar; Devarasetti, Ashok Kumar; Bobbili, Rajendar; Khurana, Amit; Veera Hanuman, Donga Durga; Gudepu, Roupesh; Guda, Swapna (Frontiers in Veterinary Science, 2025)
IntroductionThis study explored the role of Withania somnifera/Ashwagandha root extract (ARE) on important gut–microbiome parameters in healthy geriatric dogs. We hypothesized that ARE might promote a healthy gut by its adaptogenic and anti-inflammatory effects and improve vital parameters for healthy ageing.MethodsA randomized, double-blind, placebo-controlled trial was conducted in Telangana, India. Twelve healthy geriatric Beagle dogs aged 12–15 years were enrolled. The dogs were divided into two groups to receive ARE (15 mg/kg, once daily, orally, for 2 months) or a placebo control. Various parameters were assessed, including serum haematology, biochemical markers, stool parameters, and gut–microbiome parameters.ResultsThe erythrocyte counts and haemoglobin levels were significantly increased with ARE (p < 0.01 and p < 0.001). Moreover, a significant decrease in important serum liver biomarkers (alanine transaminase [ALT], aspartate transaminase [AST]; p < 0.01 and p < 0.001 at day 60) was observed in the ARE-treated dogs compared to that in the placebo control group. In addition, the levels of L-citrulline were significantly modulated by ARE intervention, whereas the intervention did not affect intestinal-type alkaline phosphatase (I-ALP), lactate, and carbamoyl-phosphate synthase (CPS). Interestingly, the faecal score reduced significantly with ARE (p < 0.001), while the faecal pH remained unaltered. Compared to the baseline, ARE significantly decreased two microbial metabolites, propionic acid, and total short chain fatty acids (SCFAs) levels after 60 days of intervention, whereas butyrate and acetic acid levels remained unchanged in the faecal samples.ConclusionIn summary, these findings suggest that ARE has gut health promoting benefits in healthy geriatric dogs by improving haematological and biochemical profiles; the levels of L-citrulline; propionic acid; and SCFA; thus, reducing age-related changes by modulating the microbiome and the associated metabolites.